Effect of Grain Structure on the Failure Mechanism of Cu/Cu3Sn Investigated Via Molecular Dynamic Simulations - Zhang, Jicheng; Jiang, Zhitao; Zhang, Yuanxiang (Frontiers in Materials, 2022)
The grain structure has a great influence on the mechanical reliability of miniaturized interconnect circuits. Under the working conditions, Cu3Sn will be the main intermetallic compound that forms during electromigration and the thermal ageing process, which can easily induce cracks between Cu3Sn and the copper pad. This paper investigated the effect of the Cu grain structure on the Cu3Sn/Cu interface reliability via molecular dynamic simulations. Single-crystal Cu, twin-crystal Cu, and polycrystalline Cu models were implemented to form the interface structure, and uniaxial tension simulations were performed at strain rates of 0.01%, 0.1%, and 0.5% ps−1 to evaluate the interfacial strength and interface failure mechanism. Results show that the polycrystalline Cu models always exhibits a lower degree of stress and shows a great ductile character. The existence of twin grain boundaries makes Cu layer more stable, and their failure processes are dominated by stair-rod type dislocations with a Burgers vector of 1/6 [110] instead of Shockley dislocations with a Burgers vector of 1/6 [112], which induce their interface models fail in Cu3Sn layer near the interface. The strain rate dependence mechanical character of both interface and grains would be the main reason of phenomenon for the difference failure character affected by grain structure and strain rate.